Studi Eksperimentasi dan Penelusuran Keefektifan dan Efisiensi Metoda dalam Proses Belajar Membaca Permulaan di Sekolah Dasar - Suparman Heru Santosa; Nyoman Dantes; Wawan Rasna; I Gusti Putu Antara; Ketut Lama (Universitas Negeri Malang, 2016)
Among the four methods of teaching reading for beginners apparently the syntetic analytic structural (SAS) method is the most effective and efficient one. The students' textbook, especially for the first graders at the first quart semester, should primarily focuss on the introduction of alphabets without inhibiting the accuracy and speed of beginning reading. These facts are concluded based on the result of the analysis of data collected from the samples of 8 primary schools (4 in the urban and the other 4 in the rural areas) comprising 160 first graders. The technic of analysis employed was two-way ANOVA.